The use of grade three external assessment results in two Gauteng public schools to improve teaching and learning. - Viljoen, Hettie Cornelia (My University, 2012)
Based on evidence of the success of data informed interventions in the literature, we undertook a qualitative case study investigation of how two public primary schools used the results of the two external assessments, the Gauteng Provincial Assessment (GPA) and the Annual National Assessment (ANA) in 2008, to improve teaching and learning. At the time of the study the Department of Basic Education (DBE) has not yet guided the schools officially how to use the results and the district participating in the study used innovative measures to assist the schools. During semi-structured interviews, the district coordinator and principal, head of department and Grade 3 Literacy and Numeracy teachers at each of the two schools helped us understand how they interacted with the results. Several reasons were given why neither of the two schools used the GPA results. The ANA results were more useful for the classroom and the district and both schools considered them in part for planning their intervention strategies for the following year. Both exercises were new to the schools and at the time of the study the DBE had not yet provided teachers with guidance on how to use the test results to improve teaching and learning. As a result the two schools studied made very little use of the ANA scores, while the GPA results were found by the teachers to be of no assistance. Instead both schools relied on their internal assessment practices. The DBE have started to address the lack of guidance on how to use the results in 2011.
Keywords: External assessment; Assessment for learning; Assessment of learning